Investigating Students’ Perceptions of Health Education Program in the Public Secondary Schools in Al Ain City, UAE - ALAYLI, RANIA SAMIR (2020)
Health education is an essential aspect of health promotion. As such, health related skills have become crucial factors of individual’s and community’s efficiency in the 21st century. Health education involves learning of knowledge, beliefs, attitudes, values, skills and competencies. Also, it is a vital measure for students to identify risk behaviors and conditions which influence them. Thus, the main components of health education are disease prevention and early detection and health information and practice. Therefore, it is encouraging students to lead a healthy lifestyle. The main purpose of the study was to investigate students’ perceptions of the newly implemented health education program in the public secondary schools in Al Ain City. A concurrent mixed method design has been used in this study. A students’ questionnaire and in-depth semi-structured interviews were implemented. The participants of the study were female students from secondary public schools within the city of Al Ain, Emirate of Abu Dhabi, in the United Arab Emirates. A students’ questionnaire was administered to the students of health education. The participants were four groups of 258 students. In-depth semi-structured interviews were conducted to five groups of 32 students’ participants. The results revealed that school health education program had a positive impact on students’ health related knowledge, skills and dispositions. There was a significant statistical difference in means of participants’ responses to the inquiry statements. Furthermore, the results showed strong correlation between the students’ perceptions of health education and the teachers’ knowledge and skills. It can be concluded that the results of the study emphasized the importance that health education is crucial to equip students with related knowledge, skills and dispositions. Moreover, students’ learning in the health education program is critical to develop healthful bodies and minds to grow into healthy adults; that is an absolute need to face this dynamic and rapid changing world.